COVID-19: Impacts on African economies – economic challenges and social safety net responses - Hannah Wanije Ryder; Angela Benefo (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2020)
The impacts of the "COVID-19 shock" on African economies are unfolding rapidly and can be expected to vary widely by country. The effects can be divided into indirect effects depending on countries' exposure to international trade, tourism and FDI in particular; and direct effects depending on the extent of health expenses and degree of "shutdown" the countries have introduced to respond to COVID-19, as well as the economy's poverty level and dependence on informal economic activity. This brief explores evidence on these effects and the most vulnerable countries in the "direct" and "indirect" categories. It also provides a summary of actions that African governments have taken as well as four "innovative ideas" to consider in future, especially to continue poverty reduction and sustainable development, as part of Africa's COVID-19 recovery plan and in partnership with development actors, including China.
Keywords: 330